1987
DOI: 10.1177/014920638701300107
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Type A Behavior Pattern on Role Overload-induced Stress and Performance Attributions

Abstract: A controlled laboratory experiment investigated the effects of Type A behavior pattern on role overload-induced stress and performance attributions. Although previous correlation studies have concluded that Type A individuals are more likely to feel stressed than Type B individuals, the present study did notfind this. The current study reports the alternative hypothesis that differences in reported stress between Type A and Type B individuals may occur because the Type A seeks out situations that are objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Numerous studies have reported a significant relationship between job strain and a linear combination of TABP and job characteristics. Froggatt and Cotton 92 revealed that type A individuals experience more stress when their work load increases, and Choo 93 found a positive relationship between job stress and TABP. Fisher, 94 however, did not find a moderating effect of TABP on the relationship of role stress to job satisfaction and performance.…”
Section: Relationship Between Personality Traits and Burnoutmentioning
confidence: 99%
“…Numerous studies have reported a significant relationship between job strain and a linear combination of TABP and job characteristics. Froggatt and Cotton 92 revealed that type A individuals experience more stress when their work load increases, and Choo 93 found a positive relationship between job stress and TABP. Fisher, 94 however, did not find a moderating effect of TABP on the relationship of role stress to job satisfaction and performance.…”
Section: Relationship Between Personality Traits and Burnoutmentioning
confidence: 99%
“…For example, previous research has examined the influence of individual differences including locus of control (Rahim and Psenicka 1996), self-efficacy , Type A behavior pattern (Froggatt and Cotton 1987), political skill (Jawahar et al 2007;Perrewé et al 2005), core self-evaluations (Harris et al 2009), and proactive personality (Cunningham and De La Rosa 2008) on the stress-strain relationship. Proactive personality is particularly relevant to how individuals perceive stressors and manage stress.…”
Section: Proactive Personalitymentioning
confidence: 99%
“…The results revealed a significant relationship between job tension and linear combination of Type A personality and job characteristics. Froggatt & Cotton (1987) observed that Type A people created more stress on themselves by increasing the volume of workload. et al, (1995) studied the direct and relative efficacy of cognitive hardiness, Type A behaviour pattern, coping behaviour and social support as predictors of stress and ill-health among 1,925 staff of an Australian University.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%